Renal Vein Thrombosis and Membranous Nephropathy - Report of 2 Cases - Daher, Elizabeth F; Silva, Geraldo B; Galdino, Gabriela S; Eduardo, Denislene S; Wanderley, Tatiana P; Lopes, Germison S (Journal of Medicine, 2011)
Patients with nephrotic syndrome presents a high risk of arterial and venous thrombosis, mainly deep vein thrombosis and renal vein thrombosis (RVT). We describe two cases of patients with diagnosis of membranous nephropathy and RVT. The first patient was 32 years, male, and admitted with nephrotic syndrome. Laboratory tests showed urea 16mg/dL, creatinine 0.9mg/dL; proteinuria 17g/day. Abdominal ultrasound evidenced obstruction of right and left renal veins and left inferior vena cava. Renal biopsy was compatible with membranous nephropathy. The second patient, a 27 years old male was admitted with nephritic syndrome. Laboratory tests at admission showed urea 25mg/dL; creatinine 1.1mg/dL; 24h proteinuria 3.86g, abdominal ultrasound showed endoluminal obstruction of left renal vein and increased size left kidney. Renal biopsy showed membranous nephropathy. RVT is not common in patients with nephrotic syndrome, and it is more frequent in membranous nephropathy. Treatment includes intravenous anticoagulant followed by oral drugs. Prophylaxis in nephritic patients is controversial. Keyword: Nephrotic syndrome; Thrombosis; Membranous glomerulonephritis; Blood coagulation DOI: 10.3329/jom.v12i1.5919 J Medicine 2011; 12 : 73-76